A simulation model for crowd evacuation of fire emergency scenario - Noor Akma, Abu Bakar; Khalid, Adam; Mazlina, Abdul Majid; Allegra, Mario (IEEE, 2017)
Human safety is an important issue when handling the crowd evacuation in order to avoid death and injuries. Human behavior changes from normal to panic behavior when they are in an emergency scenario such as building on fire. Modelling panic behavior on evacuee is a critical challenge as the human movement is unpredictable. Simulation (example: Discrete Event Simulation and Agent-Based Simulation) is a well-known method to investigate crowd evacuation. But the question here is: Which simulation method is suitable to model a realistic representation of crowd evacuation? Thus, in this paper, a simulation model based on Agent-Based Simulation (ABS) and Social Force Simulation (SFS) Model is proposed to improve on modelling fire evacuation in a closed space (building). To achieve the above research aim, three simulation models (ABS Model, SFS Model and a hybrid of ABS and SFS model) will be developed and compared. This paper will discuss on the development of conceptual model of these three simulation models. Later, the conceptual models will be used to represent the investigated simulation models.